Job apocalypse? Humbug! (Economist, 2025)
The article cites several job creations attributed to the rise of artificial intelligence (AI). These include data annotator who help train AI models, forward-deployed engineers who work as developer, consultant and salesman and also customize AI tools for clients, AI risk-and-governance specialists who ensure that bots do not leak data, and the chief AI officer who combine technical expertise with knowledge of a particular industry.